All-trans retinoic acid modulates the retinoic acid receptor-alpha in promyelocytic cells. - Chomienne, C (1991)
We have recently demonstrated that all-trans retinoic acid (RA), the active metabolite of vitamin A, is an efficient alternative to chemotherapy in the treatment of acute promyelocytic leukemia (AML3). We have further shown that, in these AML3 cells, the gene of the retinoic acid receptor-alpha (RAR alpha) is translocated from chromosome 17 to chromosome 15, and fused to a new gene, PLM. This results in the expression of both normal and chimeric RAR alpha transcripts in AML3 cells. The PLM-RAR alpha protein may account for the impairment of differentiation and thus leukemogenesis, but not for the paradoxical efficacy of RA in these cells. In an attempt to elucidate RA's differentiative effect in AML3 patients, the present work examined the in vitro and in vivo modulation of the normal RAR alpha transcripts by all-trans RA in seven cases of AML3. In all samples, Northern blot analysis revealed a low expression of the two normal RAR alpha transcripts compared with other human myeloid leukemic cells. No modulation was observed after 4-8 d of in vivo therapy with all-trans RA 45 mg/m2 per d. In vitro incubation with all-trans RA, however, increased the level of expression of the normal RAR alpha transcripts in AML3 cells but not in other AML leukemic subtypes. This modulation of the two normal RAR alpha transcripts appeared to be an early and primary event of RA's differentiating effect. We therefore suggest that up-regulation of the normal RAR alpha gene expression by pharmacological concentrations of all-trans RA may restore the normal differentiation pathway in these cells.